Australian Idiopathic Pulmonary Fibrosis Registry: Vital lessons from a national prospective collaborative project. Issue 7 (14th August 2014) - Moodley, Yuben; Goh, Nicole; Glaspole, Ian; Macansh, Sacha; Walters, E Haydn; Chapman, Sally; Hopkins, Peter; Reynolds, Paul N; Zappala, Christopher; Cooper, Wendy; Mahar, Annabelle; Ellis, Samantha; et al.
<x xml:space="preserve">Abstract</x> There is little Australian epidemiologic data on idiopathic pulmonary fibrosis (IPF), a relatively uncommon but devastating disease. The vast geographic distances in Australia have been a major impediment for collaborative research into IPF. A collaborative national effort, the Australian IPF Registry, has been formed, launched and is recruiting successfully (n = 359, January 2014). Our experience provides unique insights for others wishing to set up IPF registries and in time for a global IPF registry.